Evaluasi Kualitas Website Jawa Pos menggunakan Metode Webqual 4.0 dan Importance Performance Analysis (IPA) (Studi pada PT. Jawa Pos) - Yunior Rikky Fitanto; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT. Jawa Pos is a company which engaged in the multimedia printing daily newspaper named Jawa Pos, based in Surabaya, East Java. Furthermore Jawa Pos is also engaged in the application and the website as a media for users to read the news. The purpose of this research is to know the quality of Jawa Pos website which emphasizes on three variables, namely Usability factor, Information Quality factor, Service Interaction Quality factor on Jawa Pos website based on Webqual 4.0 method. Data collection is obtained from the dissemination of questionnaires and analysis using descriptive analysis and Importance Performance Analysis (IPA) method which assesses the performance of Jawa Pos website based on the importance of each variable. The valuation scale on this study used the Likert scale method implementing the 5 scales of choice with statements ranging from strongly disagreeing to very concur. While the technique used to measure the number of respondents needed in this study, using Slovin technique with a percentage of accuracy is 90%, so the number of respondents needed in this research is 100 respondents. To limit the scope of existing, the characteristics of the population in this study are the people who have experience using Jawa Pos websites to read the news online with sampling techniques using the approach Convenience Sampling. This research resulted in an improvement recommendation based on its factors of interest and performance.